Using social network analysis to assess the Pontocaspian biodiversity conservation capacity in Ukraine - Aleksandre Gogaladze (Resilience Alliance, 2020)
Social networks, defined as sets of relationships between stakeholder organizations, are important determinants of constructive actions for biodiversity conservation. Such actions are achieved through cooperation between various stakeholders, exchange of information, and joint planning and implementation. We used a mix of qualitative and quantitative social network analysis methods to investigate the interorganizational network of stakeholders in Ukraine, and the implications of network properties for the conservation of Pontocaspian biodiversity. Pontocaspian biota contains unique and endemic fauna, which are threatened by anthropogenic impacts; this makes effective conservation measures an urgent priority. We identified a well-connected, centralized network in Ukraine. However, the strong network has not resulted in effective conservation of Pontocaspian biodiversity. Suboptimal conservation action stems from the subordinate role of Pontocaspian species in the interorganizational interactions, likely due to lack of knowledge regarding Pontocaspian taxa. Social variables, such as funding scarcity and legal constraints, further limit the effectiveness of biodiversity conservation actions. We conclude that the current landscape of stakeholders in Ukraine is well placed to rapidly improve conservation actions if they are supplied with improved information and recognition of conservation needs of Pontocaspian taxa, combined with improved financial and legal conditions.